PENGARUH LUAS LAHAN, BIAYA PRODUKSI, DAN HARGA PASAR TERHADAP PENDAPATAN PETANI BAWANG MERAH DI JAWA TENGAH - Amrina Rosada Hardyaningtyas; Retno Indah Hernawati (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
This study aims to determine the effect of land area, production costs, and market prices on the income of red onion farmers in Central Java. This type of research is quantitative research. The data source used is primary data obtained by distributing questionnaires to farmers and secondary data from the website of the Ministry of Trade of the Republic of Indonesia, Central Java. The population in this study were red onion farmers spread across 7 regencies in Central Java with the largest harvest area including Brebes, Demak, Pati, Kendal, Temanggung, Boyolali, and Tegal Regencies. Based on the stratified random sampling and convenience sampling method, the number of respondents used was 216 shallot farmers. The data analysis technique used in this study is the multiple linear regression analysis methods with the SPSS 25 data analysis tool. The results of this study indicate that production costs and market prices affect the income of shallot farmers in Central Java while the land area does not affect the income of shallot farmers. red in Central Java.